Pemberdayaan Guru dalam Mengembangkan Metode Pembelajaran Aktif Berkarakter Islam Rahmatan Lil’alamin - Imam Mawardi; Akhmad Baihaqi; Rochim Widaryanto (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2018)
ABSTRACTThis article is the result of the community partnership program (PKM) which aims to improve teacher competency in the development of active learning methods characterized by Islam rahmatan lil'alamin at SD Muhammadiyah Pujotomo and MI Muhammadiyah Danurejo of  Mertoyudan-Magelang. These two institutions have problems, one of which is related to competence in managing learning; the teachers tend to be conventional in applying learning methods and cannot yet relate learning to Islamic approaches. Even though the content in Islamic education institutions should show the characteristics of Islamic nuances of learning. The solution to overcome this problem is to equip teachers with the active learning method with the character of Islam rahmatan lil ‘alamin; as a form of actualization of the development of teacher's pedagogical abilities. The method in this PKM uses the Participatory Rural Apraissal (PRA) model, by involving partners in determining the problem solving faced. The results obtained indicate an increase in the ability of teachers in designing and developing active learning methods characterized by the character of Islam rahmatan lil'alamin, and is an innovation step in the development of the 2013 curriculum which emphasizes the strengthening of character education. Keywords: active learning method, Islam rahmatan lil'alamin, empowering teachers ABSTRAKArtikel ini merupakan hasil dari program kemitraan masyarakat (PKM) yang bertujuan untuk meningkatkan kompetensi guru dalam pengembangan metode pembelajaran aktif berkarakter Islam rahmatan lil’alamin di SD Muhammadiyah Pujotomo dan MI Muhammadiyah Danurejo, Kecamatan Mertoyudan Kabupaten Magelang. Dua lembaga ini mempunyai masalah, salah satunya adalah berkaitan dengan kompetensi dalam mengelola pembelajaan; para guru cenderung konvensional dalam menerapkan metode pembelajaran dan belum bisa mengaitkan pembelajaran dengan pendekatan Islami. Padahal seharusnya muatan di lembaga pendidikan Islam harus menunjukkan karakteristik pembelajaran yang bernuansa islami. Solusi untuk mengatasi masalah tersebut adalah membekali para guru dengan metode pembelajaran aktif berkarakter Islam rahmatan lil ‘alamin; sebagai bentuk aktualisasi pengembangan kemampuan pedagogik guru. Metode dalam PKM ini mengunakan model Participatory Rural Apraissal (PRA), dengan melibatkan mitra dalam penentuan pemecahan masalah yang dihadapi. Hasil yang diperoleh menunjukkan adanya peningkatan kemampuan guru dalam merancang dan mengembangkan metode pembelajaran aktif berkarakter Islam rahmatan lil’alamin, dan merupakan suatu langkah inovasi pengembangan kurikulum 2013 yang mengedepankan penguatan pendidikan karakter.  Kata Kunci: metode pembelajaran aktif, Islam rahmatan lil’alamin, pemberdayaan guru